Molecular Identification and Functional Characterization of a Putrescine Hydroxycinnamoyltransferase in Suspension Cells of Bamboo (Phyllostachys nigra) - Nomura, Taiji; Kato, Yasuo (Applied biochemistry and biotechnology, 2025)
Cultured cells of a bamboo species (Phyllostachys nigra; Pn) were previously demonstrated to be a suitable host for the bioproduction of exogenous phenylpropanoid-derived compounds based on the rational metabolic-flow switching strategy. In the strategy, the biosynthetic pathway of hydroxycinnamoylputrescines, the major secondary metabolites in Pn cells, was redirected to the biosynthetic pathways of the compounds of interest through genetic transformation. To improve the efficiency of metabolic-flow switching in transgenic Pn cells, functionally disrupting the endogenous gene encoding putrescine hydroxycinnamoyltransferase (PHT), catalyzing the formation of hydroxycinnamoylputrescine, may be a promising strategy. In this study, we identified the gene (PnPHT1) encoding PHT following the purification of a native enzyme from Pn cells treated with a chitosan oligomer, an elicitor used to promote PHT production. PnPHT1 was revealed to belong to Clade IVa of the BAHD acyltransferase superfamily, similar to other PHTs, and catalyzed the formation of hydroxycinnamoylputrescines, with feruloyl-CoA and putrescine as the preferred acyl donor and acceptor, respectively. PnPHT1 transcript levels rapidly increased after Pn cells were treated with a chitosan oligomer, with peaking at 24 h, which was markedly quicker than the transcriptional induction after 10 days of culture without elicitor treatment. Combining the culture system using chitosan oligomer elicitor with PnPHT1-knockout/knockdown will increase the utility of Pn cells as a host for producing exogenous phenylpropanoid-derived compounds via rational metabolic-flow switching.